Application of Effective Microorganisms in Soil-Cement Mixtures - Petrash, Oleksandr; Petrash, Ruslan; Popovych, Nataliia (International Journal of Engineering and Technology, 2018)
This paper provides a research data on the impact of effective microorganisms on the physic and mechanical properties of soil-cement mixtures and stone. Deep soil mixing technology considered to be used for manufacturing soil-cement. The purpose of the research is to determine a way of increasing strength of soil-cement by addition of effective microorganisms. Strength increasing method should not compromise the mixture’s movability. Authors used an experimental approach within which there were standard techniques of determining the movability of soil-cement mixture and density and strength of a soil-cement stone in a laboratory environment. This research resulted in discovering the optimal contents of a soil-cement mixture with respect to mechanical properties required. Authors proved the effective microorganisms to be efficient mean of increasing the strength of soil-cement.